Pedagogical environments for the formation of research competence in students within practice-oriented chemistry education - Kanat Sadykov; Nesipkhan Bektenov; Nursulu Zhussupbekova; Ainash Baidullayeva (International Journal of Evaluation and Research in Education (IJERE), 2026)
Despite the importance of research competence in modern chemical education, traditional instructional methods often fail to sufficiently prepare students for independent scientific inquiry and professional growth, creating a gap between theoretical knowledge and practical application. The research aimed to experimentally validate a multifaceted system of pedagogical environments (research-focused, metacognitive-digital, and motivational) designed to foster research competence in chemistry students through practice-oriented learning. The research design of the research was a 30-week longitudinal pedagogical experiment utilizing a quasi-experimental design with pre- and post-test assessments. The sample comprised of 325 third- and fourth-year future chemistry teachers (experimental group (EG)=165; control group (CG)=160) from a national university in Kazakhstan. Statistical analysis (Pearson χ² test) confirmed significant growth in the EG across all competence criteria, with the proportion of students reaching “high-level” research proficiency increasing from 10.9% to 38.8%. The key implication is integrating structured pedagogical environments into teacher-training curricula effectively bridges the gap between theoretical knowledge and practical inquiry, providing a scalable framework for modernizing science, technology, engineering and mathematics (STEM) education.